2021
DOI: 10.1186/s12870-021-03040-3
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the multifunctional role of the cell wall components in the maize exploitation

Abstract: Background Besides the use of maize grain as food and feed, maize stover can be a profitable by-product for cellulosic ethanol production, whereas the whole plant can be used for silage production. However, yield is reduced by pest damages, stem corn borers being one of the most important yield constraints. Overall, cell wall composition is key in determining the quality of maize biomass, as well as pest resistance. This study aims to evaluate the composition of the four cell wall fractions (ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The composition and proportion of the subunits highly influence the molecular structure of lignin. It affects the degree of crosslinking with the polysaccharides and also the branching of the polymer, affecting, as it has been demonstrated, economically important processes such as biofuel production and digestibility. , In addition, some other related phenylpropanoids also contributed to biomass yield and anatomical traits of the stems. We have shown that a great concentration of PCA in the cell wall is unfavorable for increasing biomass yield and rind puncture resistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The composition and proportion of the subunits highly influence the molecular structure of lignin. It affects the degree of crosslinking with the polysaccharides and also the branching of the polymer, affecting, as it has been demonstrated, economically important processes such as biofuel production and digestibility. , In addition, some other related phenylpropanoids also contributed to biomass yield and anatomical traits of the stems. We have shown that a great concentration of PCA in the cell wall is unfavorable for increasing biomass yield and rind puncture resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The set of inbred lines evaluated can be subdivided into three subsets: (i) inbreed lines included in previous evaluations for resistance to Sesamia nonagrioides or Ostrinia nubilalis, (ii) inbreds used in hybrid combinations for bioenergy and for silage, and (iii) inbreds that perform well in hybrid combinations. A complete and detailed description of the inbreds evaluated can be found in ref .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, a genome-wide association study (GWAS) approach has been used to find QTL for resistance to fumonisin contamination in an eight-way MAGIC population previously used for locating QTL for FER [ 10 ]. In this MAGIC population founders have shown high diversity for specific traits, FER and fumonisin content among those traits [ 10 , 19 25 ]. In addition, MAGIC populations could be used to obtain superior breeding lines for resistance to FER and to fumonisin contamination [ 26 ], or as base materials to perform genomic selection [ 27 ].…”
Section: Introductionmentioning
confidence: 99%